SCIENTIFIC MAPPING OF CLIMATE CHANGE AND MENTAL HEALTH: A SCIENTOMETRIC ANALYSIS - Mohd Faizal Azrul Azwan Muhamed Che Harun; Mohd Azharul Azemi; Nur Fakhzan Marwan; Fazreena Mansor; Zaidatul Nadiah Abu Yazid; Azeni Abu Bakar; Jolin Norshyme Hashim; Ratha Krishnan Suppiah (Journal of Islamic, Social, Economics and Development, 2023)
The present study conducted a comprehensive examination of the body of literature about the domain of climate change and mental health. This investigation used empirical data and scientometric approaches to analyse the subject matter in detail. A thorough analysis was conducted on a large dataset consisting of more than 1353 scholarly publications in order to investigate and understand the current trends within this academic field. The Web of Science Core Collection (WoS) was used as the primary tool for identifying and examining important characteristics, such as publishing trends, citation behaviours, significant academic works, and notable terminology. Significantly, the data revealed significant participation from a wide range of 113 nations and areas in the field of climate change and mental health research. Over a period of time, noticeable patterns emerged indicating a significant increase in the level of publishing activity, with the United States, Australia, and England emerging as the primary contributors. This study has identified a group of 4,768 writers who have made major advancements to the development of this discipline. Significantly, the term "suicide" surfaced as one of the most significant keywords inside the corpus. Also, the emergence of thematic keywords such as "green space" and "place" highlights the need for greater research funding and the utilisation of innovative methodologies to stimulate the creation of novel scholarly contributions in the field of climate change and mental health.